THE VALUE OF PROGNOSTIC FACTORS FOR GLIOBLASTOMA TREATED WITH CONCURRENT THERMOCHEMORADIOTHERAPY - A. I. Ryabova; V. A. Novikov; O. V. Gribova; Zh. A. Startseva; E. G. Grigoriev; S. A. Glushchenko; A. A. Ponomaryova; V. A. Sirkashev (Сибирский онкологический журнал)
The treatment of patients with glioblastoma continues to be one of the greatest challenges. Glioblastoma is the most aggressive malignant primary brain tumor and is the most lethal among all cancers. Despite advances in the standard treatment, the prognosis for patients with glioblastoma remains poor, therefore, the development of novel treatment strategies is required.Material and methods. Our study included 30 patients with newly diagnosed glioblastoma, who underwent concurrent chemoradiotherapy and local hyperthermia.Results. The median disease-free and overall survival rates were 9.6 months and 23 months, respectively. The analysis of clinical, molecular-genetic and prognostic factors related to treatment modality showed statistically significant differences in survival between patient groups representing different times for starting adjuvant therapy after surgery. The median disease-free survival was significantly higher in patients who received chemoradiotherapy with local hyperthermia within 6 weeks after surgery than in patients who started adjuvant treatment earlier. The overall survival rate was statistically higher in patients receiving a special treatment for tumor recurrence compared to that in patients receiving symptomatic therapy. The evaluation of molecular-genetic prognostic factors showed no statistically significant differences in survival among patients with methylated and nonmethylated MGMT promoter. The presence of IDH1 mutations was identified in only one case. Evaluation of prognostic factors does not allow identification of clinical and molecular biological factors that group patients with hypersensitivity to the proposed treatment regimen. However, high rates of overall and disease-free survival, even in patients with non-methylated MGMT, allow us to recommend this treatment modality for patients with newly diagnosed glioblastoma.